Structure‐Based Drug Design: Identification of Glucokinase Activators from Natural Compounds for the Treatment of Type 2 Diabetes. Issue 15 (14th April 2023) - Malini, Manokaran; Thilagavathi, Ramasamy; Kumar Singh, Sanjeev; Pravin, Arun; Selvam, Chelliah
Abstract: Glucokinase Activators (GKA) are novel small molecules that target GK and reduce plasma blood glucose by binding GK allosterically. It is considered as a potential therapeutic target to treat T2D. So, in an effort to identify compounds to treat T2D efficiently, a structure‐based virtual screening was performed on compounds from Universal Natural Product Database (UNPD) using FRED. Among 229358 compounds from UNPD, four compounds were identified as potential small molecules. The hit compounds UNPD 1354, UNPD 85595, UNPD 6604, and UNPD 88147 are found to interact strongly with active site residues ARG 63, VAL62, VAL452, TYR215, VAL 455, MET210, MET235, and TYR214. In addition, ADME predictions show that the compounds satisfy drug‐likeness criteria. Finally, the molecular dynamics simulation was carried out for 50 ns using the GROMACS 2020 package, the results confirm the stability of the enzyme‐HIT throughout the simulation time. Thus, this study may provide valuable insights into identifying novel small molecules as GKAs. Abstract : In this study, 229358 natural compounds from the Universal Natural Product Database were screened initially using FRED. Four compounds from a pool of 500 top hits were identified as potential glucokinase activators by the docking results. The four compounds were submitted to molecular dynamics for 50 ns after the ADME analysis revealed that all four compounds met the requirements for drug‐likeness. The simulation results showed that all four compounds were quite stable over the course of the study. The UNPD 88147 hit chemical had an average RMSD and RMSF value of 0.4 nm and 0.5 nm, and it had the highest chemguass4 score of −15.51 when compared to other hits.